2009
DOI: 10.1152/ajpheart.00256.2009
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic automatic activity in the rat pulmonary vein: electrophysiological differences between cardiac muscle in the left atrium and pulmonary vein

Abstract: Doisne N, Maupoil V, Cosnay P, Findlay I. Catecholaminergic automatic activity in the rat pulmonary vein: electrophysiological differences between cardiac muscle in the left atrium and pulmonary vein. Am J Physiol Heart Circ Physiol 297: H102-H108, 2009. First published May 8, 2009 doi:10.1152/ajpheart.00256.2009.-Ectopic activity in cardiac muscle within pulmonary veins (PVs) is associated with the onset and the maintenance of atrial fibrillation in humans. The mechanism underlying this ectopic activity is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 37 publications
8
62
2
5
Order By: Relevance
“…Adrenoceptor-mediated changes in RP were also reported in the rat pulmonary vein myocardium, and mechanisms such as β-adrenergic receptor stimulation-induced activation of (17). Induction of automatic activity by noradrenaline in most of the quiescent preparations ( Fig.…”
mentioning
confidence: 61%
“…Adrenoceptor-mediated changes in RP were also reported in the rat pulmonary vein myocardium, and mechanisms such as β-adrenergic receptor stimulation-induced activation of (17). Induction of automatic activity by noradrenaline in most of the quiescent preparations ( Fig.…”
mentioning
confidence: 61%
“…Interestingly, Findlay et al, 33 working with isolated multicellular rat LA and pulmonary vein sleeve preparations, have recently demonstrated a sustained hyperpolarization of the resting membrane potential in response to selective β-adrenoceptor stimulation, consistent with a β-adrenoceptormediated increase in K + -selective background conductance. Moreover, ISO has been reported to shorten APD in LA from normal mice.…”
Section: Mechanism Of Atrial K Atp Channel Activationmentioning
confidence: 98%
“…The most obvious difference was that PV cardiac muscle cells had a lower resting membrane potential (RMP). We have previously reported that there was little difference between the action potentials (AP) evoked by electrical stimulation (2 Hz) in the rat PV and LA cardiomyocytes . However, the RMP in the PV rose following the cessation of electrical stimulation to a steady‐state level that was clearly depolarized (‑70 ± 1 mV) compared with the LA (‐85 ± 2 mV), suggesting that PV cardiomyocytes might have a higher basal permeability to Na + .…”
Section: Introductionmentioning
confidence: 99%